Penerapan Model Pembelajaran ASSURE dalam Analisis Materi Pembelajaran Tematik Kelas 3 Subtema 1 Pembelajaran 1 - Hasanah, Fadilatul (Pendidikan Islam Pascasarjana IAIN Jember, 2023)
The ASSUR learning model which stands for components or important steps contained in several concepts in it, including; A = Analize learner characteristics, S = State performance objectives, S = Select method, media, and materials (selecting methods, media, and teaching materials), U = Utilize technology, media, and materials (utilizing media, technology, and teaching materials), R = Requires learner participation (involving learner participation), E = Evaluate and revise. This model is suitable for use in analyzing the learning material to be taught. In this case, researchers are interested in conducting research on the Application of Assure Learning Models in the Analysis of Thematic Learning Materials Grade 3 Soup Theme 1 Learners 1. The purpose of this study is to find out the material to be taught from the teacher's book. From the results of our analysis of the Application of the Assure Learning Model in the Analysis of Thematic Learning Materials for Grade 3 Soup Theme 1 Learners 1. We can conclude that in the Thematic material of Class 3 Sup Theme 1 Learner 1 which teaches about the growth and development of living beings in the material is divided into 3 materials, namely, mathematics, B.Indonesia, and SBDP. In learning activities, the theme has been arranged and in accordance with the ASSUR learning model which stands for components or important steps contained in several concepts in it, including; A = Analize learner characteristics, S = State performance objectives, S = Select method, media, and materials (selecting methods, media, and teaching materials), U = Utilize technology, media, and materials (utilizing media, technology, and teaching materials), R = Requires learner participation (involving learner participation), E = Evaluate and revise.